Marketing Strategy to Increase Sales of Traletosi Coffee in Lembantongoa Village - Siti Aisyah Andini; Syamsul Bahri Dg. Parani; Zakiyah Zahara; Moh. Zeylo A. (PT. Global World Scientific, 2024)
This research aims to find out and analyze the strategies used by the Traletosi ground coffee business to increase sales. The method used is a qualitative method and SWOT analysis (Strength, weakness, opportunity, threat). SWOT analysis is an analysis used to evaluate opportunities and threats in the external environment as well as strengths and weaknesses in the internal environment. The main focus of this research is on the mix of Segmentation, Targeting, Positioning, and Marketing. The research results obtained are the increasing use of strategy in marketing a product, the driving factor of which is generating greater profits or profits. The strategic analysis tool used to evaluate IFAS ( Internal Factor Analysis Summary) and EFAS (External Factor Analysis Summary) to evaluate internal and external factors that influence a business in the context of the Traletosi coffee business, by creating IFAS and EFAS tables as a marketing strategy to increase sales.